Hippocampal subregion-specific microRNA expression during epileptogenesis in experimental temporal lobe epilepsy - Gorter, Jan A.; Iyer, Anand; White, Ian; Colzi, Anna; van Vliet, Erwin A.; Sisodiya, Sanjay; Aronica, Eleonora (Neurobiology of disease, 2014)
Since aberrant miRNA expression has been implicated in numerous brain diseases, we studied miRNA expression and miRNA regulation of important signaling pathways during temporal lobe epileptogenesis in order to identify possible targets for epilepsy therapy. The temporal profile of miRNA expression was analyzed in three brain regions (CA1; dentate gyrus, DG; parahippocampal cortex, PHC) associated with epileptogenesis in a rat model for temporal lobe epilepsy. Tissue was obtained after electrically-induced status epilepticus (SE) at 1day (n=5), 1week (n=5) and 3-4months (n=5), and compared with control tissue (n=10) using the Exiqon microRNA arrays which contain capture probes targeting all miRNAs for rat (p<0.01, and a 1.5 fold up- or downregulation). Expression of three blood plasma miRNAs from the same group of rats was also investigated in rats in order to determine whether plasma miRNAs could serve as potential biomarkers of the epileptogenic process. Molecular pathways potentially altered by the expression of multiple miRNAs were identified using a web-based algorithm, DIANA. In CA1 and DG, more upregulated than downregulated miRNAs were present during each stage after SE. The highest numbers of upregulated miRNAs were encountered during the chronic stage in the DG. In PHC, a high number of downregulated miRNAs were detected. Key pathways involved, based upon quantitatively altered miRNA expression were: axon guidance, MAPK signaling pathway, focal adhesion, TGFβ, ErbB-, Wnt- and mTOR signaling, and regulation of actin skeleton. Expression of plasma miRNAs was differentially regulated after induction of SE. This study identified several signaling pathways possibly involved in temporal lobe epileptogenesis, not previously indicated by RNA microarray studies. These include miRNAs that regulate the ErbB and Wnt pathways and focal adhesion, which may represent interesting new targets for therapeutic interventions. •Dynamic miRNA expression changes are observed during epileptogenesis in hippocampal subregions.•miRNA expression profiles showed stage-specific changes in miRNA expression.•Expression of miRNA 146a, miR21 and miR142 is altered during epileptogenesis in both tissue and plasma.•miRNAs that regulate the ErbB and Wnt pathways and focal adhesion emerge as interesting new targets.